Pengaruh Perceived Usefulness, Perceived Ease of Use dan Perceived Price terhadap Customer Loyalty melalui Customer Satisfaction pada Pengguna Aplikasi Ojek Online Grab di Kota Bandung - Nuraeni, Putri; Evangalista, Leni (Universitas Batanghari, 2024)
With the advent of online transportation services, society has embraced a more modern way of life. People can easily order rides through their smartphones, making use of user-friendly apps that are accessible for both Android and iOS users. This convenience has led to widespread adoption of online transportation services among the public, especially in cities like Bandung where residents have busy schedules that rely heavily on such services. Apps like Grab and Gojek are particularly popular in Indonesia, with Grab ranking second after Gojek in terms of user base among online transportation apps in the country. Despite its popularity, Grab has experienced a 1.4% decrease in its Top Brand index. Therefore, this research aims to evaluate how the Perceived Usefulness, Perceived Ease of Use, and Perceived Price of the Grab app in Bandung influence Customer Loyalty through Customer Satisfaction, based on a study involving 150 users of the app. The findings of this study are expected to guide future research and assist similar companies in designing better strategies to enhance service quality.